O'Brien actinic granuloma: A case report and brief review of literature - Inês D Coutinho; Leonor I C Ramos; Maria M Brites; Oscar Tellechea (Wolters Kluwer Medknow Publications, 2015)
O'Brien first described the actinic granuloma in 1975, as an infrequent granulomatous disorder occurring in sun-exposed skin, with a slow but often self-limited course. Ever since its initial description, the actinic physiopathogenic hypothesis has been debated by many authors. We report a 60-year-old female rural worker that presented with a 14 × 7 cm annular lesion with erythematous elevated borders and an atrophic center on the right calf. The lesion was evolving for 2 years, and histopathology confirmed actinic granuloma. She started acitretin with halting of disease progression after 6 months of therapy. Our case can also be associated to actinic damage, despite its unusual location, therefore highlighting the role of solar elastosis in the development of O'Brien actinic granuloma.